On the Equivalence of B-Rigidity and C-Rigidity for Quasitoric Manifolds - Jin Hong Kim (International Journal of Mathematics and Mathematical Sciences)
For quasitoric manifolds and moment-angle complexes which are central objects recently much studied in toric topology, there are several important notions of rigidity formulated in terms of cohomology rings. The aim of this paper is to show that, among other things, Buchstaber-rigidity (or B-rigidity) is equivalent to cohomological-rigidity (or C-rigidity) for simple convex polytopes supporting quasitoric manifolds.